To determine which pair of expressions are equivalent, let's simplify each pair one by one.
-
-3(x + 2) and -6x - 3: \[ -3(x + 2) = -3x - 6 \] Comparing this with \(-6x - 3\), they are not equivalent.
-
3x + 2x and x^2(3 + 2): \[ 3x + 2x = 5x \] \[ x^2(3 + 2) = x^2 \cdot 5 = 5x^2 \] Comparing \(5x\) and \(5x^2\), they are not equivalent.
-
3x + 2 and 3(x + 2): \[ 3(x + 2) = 3x + 6 \] Comparing \(3x + 2\) and \(3x + 6\), they are not equivalent.
-
3(x + 2) and 3x + 6: \[ 3(x + 2) = 3x + 6 \] These two expressions are equivalent.
Therefore, the pair of equivalent expressions is 3(x + 2) and 3x + 6.